2006
DOI: 10.1364/josaa.23.000267
|View full text |Cite
|
Sign up to set email alerts
|

Optical image processing using the photoinduced anisotropy of pyrrylfulgide

Abstract: A synthesized photochromic compound-pyrrylfulgide--is prepared as a thin film doped in a polymethylmethacrylate (PMMA) matrix. Under irradiation by UV light, the film converts from the bleached state into a colored state that has a maximum absorption at 635 nm and is thermally stable at room temperature. When the colored state is irradiated by a linearly polarized 650 nm laser, the film returns to the bleached state; photoinduced anisotropy is produced during this process. Application of optical image processi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…These are the two spectrally separated photochromic forms, whose molecular formulas are shown in Fig.9. In this film we also found the photo-induced anisotropy property [4] . The absorption of the C-form (A C (λ)) and E-form film (A E (λ)) were measured using a UV-VIS-IR spectrophotometer (UV-3101PC, Shimadzu Inc., Japan), which were shown in Fig.10a.…”
Section: Photochroism and Photo-induced Anisotropy Of 3-indoly-benzylsupporting
confidence: 55%
See 2 more Smart Citations
“…These are the two spectrally separated photochromic forms, whose molecular formulas are shown in Fig.9. In this film we also found the photo-induced anisotropy property [4] . The absorption of the C-form (A C (λ)) and E-form film (A E (λ)) were measured using a UV-VIS-IR spectrophotometer (UV-3101PC, Shimadzu Inc., Japan), which were shown in Fig.10a.…”
Section: Photochroism and Photo-induced Anisotropy Of 3-indoly-benzylsupporting
confidence: 55%
“…We found that there exists photo-induced anisotropy in fulgide-doped polymeric films [4] , which can be used in polarization holography application. When the colored states are irradiated by a linearly polarized 650 nm laser, the films returns to the bleached states and photo-induced anisotropy is produced during this process.…”
Section: The Photo-induced Anisotropy Of Fulgide Filmsmentioning
confidence: 90%
See 1 more Smart Citation
“…Simply by placing a polarizer sheet at the Fourier plane, Ferrari et al demonstrated phase visualization and edge enhancement [27]. Most recently, Menke et al demonstrated optical image processing using photoinduced anisotropy property of pyrrylfulgide [28].…”
Section: Photoinduced Anisotropy For Medical Image Processingmentioning
confidence: 99%
“…In bR, switching between B and M states are used to create the photoinduced anisotropy. Similarly in azobenzene molecules, trans-cis isomerization states are exploited, whereas pyrrylfulgide operates between its two states -bleached state (E-form) and colored state (C-form) [28].…”
Section: Photoinduced Anisotropy For Medical Image Processingmentioning
confidence: 99%